Shelter of the most high [large type] - Cossette, Connilyn (Thorndike Press large print Christian historical fiction, 2018)
"Daughter of a pagan high priest, Sofea finds solace in the freedom of the ocean. When marauders attack her village on the island of Sicily, she and her cousin are taken to the shores of Canaan. Eitan has lived in Kedesh, a City of Refuge, for eleven years, haunted by a childhood tragedy and the boundaries placed on him. He's captivated by Sofea, but revealing his most guarded secret could draw her into the danger of his past. With threats outside the walls and traitors within, Sofea and Eitan are plunged into the midst of a murder plot. Will they uncover the betrala to save themselves and those they love?" -- page 4 of cover.